El muñeco de jengibre - Aylesworth, Jim.; McClintock, Barbara (New York : Scholastic Press, 2002)
A freshly baked gingerbread man escapes when he is taken out of the oven and eludes a number of pursuers until he meets a clever fox.
Keywords: Gingerbread men -- Juvenile literature; Fairy tales; Folklore -- Juvenile literature